Effect of Soy Proteins on the Growth of Clostridium perfringens - Busta, F. F. (1971)
Proteins that are used to fabricate imitation foods such as synthetic meats were evaluated for stimulative or inhibitory effects on the growth of Clostridium perfringens. Growth rate and extent were measured in thioglycolate medium without dextrose. This liquid medium contains Trypticase (BBL) which served as the protein control. For comparison, various soy proteins, synthetic meats, beef, turkey, sodium caseinate, and combinations of each were substituted for Trypticase. Meat loaf systems were also employed to determine the effects of protein additives to meat under actual meat loaf conditions. Growth of C. perfringens type A, strain S40, was measured in the respective media at 45 C at a pH of 7.0 and an E(h) of below −300 mv. Viable populations were enumerated by agar plate techniques on Trypticase-sulfite-yeast-citrate-agar incubated anaerobically (90% N(2)-10% CO(2)) for 18 hr at 35 C. When compared to Trypticase, some soy proteins had stimulative effects on the growth of C. perfringens, whereas sodium caseinate and some soy proteins were inhibitory. In liquid medium in which meat or soy meat was the source of protein, there was a marked stimulation by beef, chicken, and soy beef. Soy chicken supported growth at a rate less than observed with Trypticase. Under actual meat loaf conditions, the addition of soy meat or protein additives to beef did not affect the growth of C. perfringens. The addition of protein additives to turkey meat loaves significantly enhanced the rate of growth of C. perfringens. The stimulative effects of some soy proteins are significant in relation to control of foodborne disease.